Keanekaragaman dan Kelimpahan Arthropoda Predator pada Lahan Pertanian Bawang Merah dalam Upaya Penyusunan Petunjuk Praktikum Ekologi - Suhadah, Suhadah (Biocaster : Jurnal Kajian Biologi, 2023)
Species diversity is a community level characteristic based on species abundance which can be used to describe community structure. Arthropoda is the largest phylum of the animalia kingdom and the number of species in Arthropoda is more than all the species from other phyla. This research is a descriptive explorative research. The aim is to determine the level of diversity and abundance of arthropods in shallot farming land in an effort to prepare ecological practical guidelines. Arthropod species catching technique uses the pitfall trap method. The results of this study were found to be 4 species of arthropods from two classes with a total number of 47 individuals found. The index of diversity of arthropods in shallot farming was low (H' < 3) and the analysis of the abundance index of one species of arthropods had a high abundance index, while the other two species had a moderate abundance index and one species had a low abundance index. The types of arthropods found on shallot farms are: 1) Spodoptera exigua L.; 2) Valanga sp.; 3) Lilioceri L.; and 4) Pass sp. The results of the validation by a team of expert validators and the readability test by 20 students concluded that they did not need revision (80% were in the good category and were suitable for use).